Function and regulation of the Arp2/3 complex during cell migration in diverse environments. (October 2016) - Swaney, Kristen F; Li, Rong
Abstract : As the first de novo actin nucleator discovered, the Arp2/3 complex has been a central player in models of protrusive force production via the dynamic actin network. Here, we review recent studies on the functional role of the Arp2/3 complex in the migration of diverse cell types in different migratory environments. These findings have revealed an unexpected level of plasticity, both in how cells rely on the Arp2/3 complex for migration and other physiological functions and in the intricate modulation of the Arp2/3 complex by other actin regulators and upstream signaling cascades.